2014
DOI: 10.1371/journal.pone.0095396
|View full text |Cite
|
Sign up to set email alerts
|

Translational Control of Arabidopsis Meristem Stability and Organogenesis by the Eukaryotic Translation Factor eIF3h

Abstract: Essentially all aboveground plant tissues develop from the stem cells in the primary shoot apical meristem. Proliferation of the stem cell population in the Arabidopsis shoot apical meristem is tightly controlled by a feedback loop formed primarily by the homeodomain transcription factor WUSCHEL (WUS) and the CLAVATA ligand-receptor system. In this study, it is shown that mutation of a translation initiation factor, eIF3h, causes a tendency to develop a strikingly enlarged shoot apical meristem with elevated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…For example, ascorbate feedback regulation using the uORF was found for an enzyme of the ascorbate biosynthesis pathway (Laing et al ., ). uORFs were also found to be implicated in plant development (Zhou et al ., ). Our work with the eEF1α uAUG showed that the uAUG mutation into uAUC induced simultaneously the loss of the o‐uORF, efficient translation and efficient targeting of the messenger to the mitochondrial surface.…”
Section: Discussionmentioning
confidence: 97%
“…For example, ascorbate feedback regulation using the uORF was found for an enzyme of the ascorbate biosynthesis pathway (Laing et al ., ). uORFs were also found to be implicated in plant development (Zhou et al ., ). Our work with the eEF1α uAUG showed that the uAUG mutation into uAUC induced simultaneously the loss of the o‐uORF, efficient translation and efficient targeting of the messenger to the mitochondrial surface.…”
Section: Discussionmentioning
confidence: 97%
“…The presence of a uORF generally reduces the level of translation of the mORF, due to efficient initiation of translation of the uORF and limited initiation at the mORF. DNA microarray analysis of mRNA present on polysomes isolated from eIF3h mutants suggested that eIF3h is necessary for reinitiation on mRNAs with uORFs (Kim et al, 2004;Kim et al, 2007;Roy et al, 2010;Zhou et al, 2010a;Zhou et al, 2014a). Numerous studies document uORFs that regulate mORF translation in plants, including several that exert their regulation based on metabolite availability .…”
Section: Eif3 and Initiation/reinitiationmentioning
confidence: 99%
“…uORF-containing mRNAs of Arabidopsis include those encoding the S class of bZIP transcription factors and Auxin Response Factors (ARFs) (Kim et al, 2004;Nishimura et al, 2005;Rahmani et al, 2009). Both eIF3h and the 60S ribosomal protein RPL24 are required for efficient reinitiation of translation of the AtbZIP11 (ATB2) and ARF mORF (Kim et al, 2004;Nishimura et al, 2005;Kim et al, 2007;Roy et al, 2010;Zhou et al, 2010a;Zhou et al, 2014a), although global analyses of polysomal RNA do not strongly support a role of RPL24 in this process (Tiruneh et al, 2013).…”
Section: Eif3 and Initiation/reinitiationmentioning
confidence: 99%
“…In zebrafish, a mutant 3h form results in the loss of translation of a number of lensassociated crystallin isoform mRNAs [134]. In the plant Arabidopsis, 3h plays an important role in enabling the translation of mRNAs possessing upstream open reading frames (uORFs) [135]. How 3h functions in these cases has not been elucidated, however.…”
Section: Eif3hmentioning
confidence: 99%